Detecção de enzimas e genes envolvidos na degradação de gelana em bactérias de solo da Amazônia - Azevedo, Izabella Monteiro Rizzi de (2019)
Gellan gum is a polysaccharide produced by soil bacteria and is used as a solidifying agent in microbiology and food industry. In a previous study bacterial cultures of the Amazonian soil showed gellan degradation in culture medium. Gellan depolymerization has already been described in Bacillus sp GL-1 and occurs with the breakdown of gellan in tetramers as a result of the activity of the enzyme gellan lyase; subsequent hydrolysis of the tetramer into monomers are then achieved by the activities of α-L-rhaminosidase, β-glucosidase and UGH. Since the Amazonian bacteria exhibited the degradation phenotype, it was hypothesized that this metabolism involved the same enzymes described in the literature. This hypothesis was tested by: 1. The search of the genes encoding the enzymes involved in the degradation of gellan and 2. The detection of enzymes in culture samples. The bacterium of the genus Mucilaginibacter P72A10 2.2 showed slow growth and loss of degradation phenotype, however, its genomic analysis revealed the presence of all the genes involved. The mixed cultures P72A10 1.2b, P72A1 2.3c, P72A1 2.3a and P72A10 1.2a which did not show all genes required for gellan degradation, were able to degrade in culture. Protein extraction was impaired by the viscosity of the gellan, however the use of an Amicon filter (100kDa) prior to extraction resulted in the reduction of this viscosity, allowing gel analysis and detection of β-glucosidase activity. Although the bacterium P72A10 2.2. presented the necessary genes for gellan degradation, it does not remain stable a pure culture. However, mixed cultures that do not have all genes necessary for gellan degradation, may establish a syntrophic relationship between them, resulting in the gellan degradation phenotype observed in the present study.